Snooze-o-rama : the strange ways that animals sleep - Birmingham, Maria (Owlkids Books, 2021)
"Just like people, animals have their own sleep routines--but in the wild, these bedtime habits are a little wackier than the teeth brushing and pj-donning that you're used to. Maria Birmingham's latest book project, Snooze-O-Rama, draws playful comparisons between the ways humans and animals sleep, bringing a new angle of interest to an aspect of children's daily routines that they might otherwise take for granted. Each animal snooze fact is prompted by something that kids do in their own bedtime routine, making the STEM content relatable and hilarious to kids! Kyle Reed's vibrant collage style illustrations bring the animals to life with colour and personality, cleverly connecting the bridge between the animal and human comparison. Examples from the book: -"While you cover yourself with a blanket ... an otter wraps itself in seaweed" -"While you doze off on a long trip ... a frigate bird nods off as it soars." -"While you pull on your pj's ... a parrotfish snuggles up in slime.""--